Growth of the mangrove species Rhizophora stylosa Griff. at its southern latitudinal limit in eastern Australia - Wilson, Nicholas C.; Saintilan, Neil (Aquatic botany, 2012)
► This is apparently the first growth study of a mangrove tree species at the polar limits of its range. ► Leaf phenology shows seasonal patterns that generally accord with tropical Queensland studies. ► Growth is successful, with no detectable variation in leaf gain over the last 265km of range. ► Growth compares to tropical studies using a comparable measure, but leaf longevity may be longer. ► Successful growth supports a hypothesis that the latitudinal limit is not a physiological one. A study on the growth of Rhizophora stylosa Griff. was undertaken in three estuaries spanning the southernmost 265km of its range at its latitudinal limit in eastern Australia. A shoot tracking methodology was devised to follow vegetative phenological patterns and branching and to derive indices of relative growth between trees. Despite an apparent expansionary phase in distribution and a recent increased trend in mean temperature, comparisons of growth in the three estuaries do not suggest a latitudinal cline. The phenologies of leaf gain and leaf loss are generally comparable between R. stylosa in New South Wales and elsewhere, as is the rate of growth assessed by leaf initiation. However, leaf longevity and the number of leaves held on the shoot appears to be overall greater in NSW than in lower latitudes, perhaps as an adaptive response to lower levels of assimilation. This study suggests that R. stylosa is not close to physiological limits at the end of its range, supporting a contention that its current known southern limit is not at an absolute thermal boundary.